2019
DOI: 10.1128/msphere.00109-19
|View full text |Cite
|
Sign up to set email alerts
|

Genome Editing of Babesia bovis Using the CRISPR/Cas9 System

Abstract: Babesia bovis, the most virulent causative agent of bovine babesiosis, is prevalent in tropical and subtropical regions of the world. Although the whole-genome sequence was released more than a decade ago, functional analysis of the genomics of this parasite is hampered by the limited breadth of genetic engineering tools. In this study, we implemented the clustered regularly interspaced short palindromic repeat (CRISPR)/Cas9 system for B. bovis and demonstrated its potential for genome editing. Cas9 and human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 30 publications
(38 reference statements)
0
23
0
Order By: Relevance
“…The CRISPR/Cas9 system was employed to delete BBOV_III004280 or insert myc and glmS sequences into the 3' end of the original locus [56]. Briefly, homologous regions (HRs) were PCR-amplified from B. bovis genomic DNA and inserted into the BamHI site of the BbU6-Cas9-hDHFR plasmid.…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…The CRISPR/Cas9 system was employed to delete BBOV_III004280 or insert myc and glmS sequences into the 3' end of the original locus [56]. Briefly, homologous regions (HRs) were PCR-amplified from B. bovis genomic DNA and inserted into the BamHI site of the BbU6-Cas9-hDHFR plasmid.…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…As ticks and tick-borne parasitic diseases become emerging concerns for humans and domestic and wild animals, the development of integrated strategies to control simultaneously ticks and tick-borne parasites are urgently needed. Genetically modified parasites produced by gene manipulation methods have been used to develop novel next generation strategies aimed at controlling vector-borne diseases [ 33 , 34 , 35 ]. Furthermore, a recent study demonstrated stable incorporation of heterologous genes into the B. bovis genome and expression of foreign proteins on the surface of parasite merozoites [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, state-of-the-art technologies, such as next-generation and nanopore sequencing approaches, can help our understanding of the composition of local strains, population dynamics of the parasites, and help identify virulence factors that can be used for developing novel vaccines. These techniques combined with gene manipulation techniques already available for the transfection of Babesia parasites [ 156 , 159 ] may also lead to better defined and non-tick transmissible live vaccines incorporating DIVA markers to differentiate vaccinated from naturally-infected animals. These DIVA vaccines are much needed in Turkey, especially considering the importation of a large number of live cattle from countries that are endemic for bovine babesiosis.…”
Section: Current Gaps On Bovine Babesiosis Research In Turkey and mentioning
confidence: 99%